Unlocking Profitability in Indonesian Banks: The Impact of Liquidity and Working Capital Turnover: Menguak Profitabilitas di Perbankan Indonesia: Dampak Likuiditas dan Perputaran Modal Kerja - Rizaldy, Rahmat; Hariasih, Misti (Indonesian Journal of Law and Economics Review, 2023)
This scientific article examines how liquidity, leverage, and working capital turnover affect profitability in the Indonesian banking sub-sector financial companies listed on the Indonesia Stock Exchange between 2017 and 2021. The study used a sample of 15 companies selected randomly, and data analysis was done using SPSS version 22 for Windows. The results indicate that liquidity and working capital turnover significantly impact profitability, either partially or simultaneously. However, the adjusted R-square test revealed that only 14.8% of the variation in profitability is influenced by these variables, while the remaining 85.2% is influenced by other factors not studied in this research. The implication of this study is that Indonesian banking sub-sector financial companies should focus on improving liquidity and working capital turnover to increase profitability. Highlights: Liquidity and working capital turnover have a significant impact on profitability in the Indonesian banking sub-sector financial companies. Improving liquidity and working capital turnover can increase profitability in these companies. Other factors not studied in this research also play a significant role in influencing profitability in the Indonesian banking sub-sector financial companies.